Risk factor paradox: No prognostic impact of arterial hypertension and smoking in patients with ventricular tachyarrhythmias - Weidner, Kathrin; Behnes, Michael; Rusnak, Jonas; Taton, Gabriel; Schupp, Tobias; Reiser, Linda; Kern-Bollow, Armin; Reichelt, Thomas; Ellguth, Dominik; Engelke, Niko; Kuche, Philipp; Hoppner, Jorge; et al. (Cardiology journal, 2020)
BACKGROUND: Data regarding the outcome of patients with ventricular tachyarrhythmias related to arterial hypertension (AHT) and smoking is limited. The study sought to assess the prognostic impact of AHT and smoking on survival in patients presenting with ventricular tachyarrhythmias. - METHODS: All consecutive patients surviving ventricular tachycardia (VT) and ventricular fibrillation (VF) upon admission to the University Medical Center Mannheim (UMM), Germany from 2002 to 2016 were included and stratified according to AHT and smoking by propensity score matching. The primary prognostic endpoint was all-cause mortality at 30 months. - RESULTS: A total of 988 AHT-matched patients (494 each, with and without AHT) and a total of 872 smoking-matched patients (436 each, with and without smoking) were included. The rates of VT and VF were similar in both groups (VT: AHT 60% vs. no AHT 60%; smokers 61% vs. non-smokers 62%; VF: AHT 35% vs. no AHT 38%; smokers 39% vs. non-smokers 38%). Neither AHT nor smoking were associated with the primary endpoint of long-term all-cause mortality at 30 months (long-term mortality rates: AHT/no AHT, 26% vs. 28%; log-rank p=0.525; smoking/non-smoking, 22% vs. 25%; log-rank p = 0.683). - CONCLUSIONS: Paradoxically, neither AHT nor smoking were associated with differences of long-term all-cause mortality in patients presenting with ventricular tachyarrhythmias.